Prevention of cisplatin-induced hearing loss in children: achievements and challenges for evidence-based implementation of sodium Thiosulfate - Meijer, Annelot J. M.; Diepstraten, Franciscus A.; van den Heuvel-Eibrink, Marry M.; Bleyer, Archie (Frontiers in Oncology, 2024)
Ototoxicity is a devastating direct, irreversible side effect of platinum use in children with cancer, with its attendant effect on speech, language and social development, quality of life and adult productivity. Cisplatin, an essential chemotherapeutic agent for the treatment of solid tumors in children is a DNA cross-linking agent. It kills both tumor cells as well as sensitive normal cells, particularly the outer hair cells of the inner ear or cochlea, by creating radical superoxides inside the cell. It is known to accumulate in the cochlea for months to years. Fortunately, to prevent hearing loss, which occurs in about 50-70% of cisplatin treated children, sodium thiosulphate (STS), which binds to cisplatin, and reduces the superoxides in both tumor and outer hair cells of the cochlea has now been discovered to be an effective and safe otoprotectant if administered correctly. The aim of this perspective paper is to explore the key safety issues and challenges important for pediatric oncologists and pharmacists when considering the clinical use of STS as an otoprotectant for children and adolescents receiving cisplatin. These include the choice of the formulation, the timing, both that of the STS in relation to cisplatin as well as the timing of the cisplatin infusion itself, the dosing, the challenge left by the definition of localized versus disseminated disease and the difference in indication for STS, between cisplatin treated patients and those receiving another platinum chemotherapeutic agent, carboplatin.